Effect of Folate Diet on Liver Metabolomics in Wild Type and Aldh1l1 Knockout Mice. (7th June 2021) - Sharma, Jaspreet; Rushing, Blake; Krupenko, Natalia; Sumner, Susan; Krupenko, Sergey
Abstract: Objectives: The goal of the present study was to investigate whether dietary folate restriction exacerbates the metabotype associated with the KO. Methods: Hepatic tissues from wildtype ( Aldh1l1 +/+ ) and KO ( Aldh1l1 − / − ) mice fed a control (CD), or folate deficient diet (FDD) for 16 weeks were profiled using untargeted metabolomics to identify metabolite changes and affected pathways. Results: PCA plots of the 6595 peaks in the preprocessed liver datasets show tight clustering of samples within the groups and clear separation between genotypes, and diets. OPLS-DA analysis showed strong separation between pairwise comparisons of the groups with model statistics (R2X, R2Y, and Q2) all greater than 0.5, indicating that dietary folate and Aldh1l1 alone or in combination have a significant effect on the liver metabolomes in male and female mice. Using MetaboAnalyst for pathway analysis significant differences in bile acid metabolism, nucleotide metabolism, and protein synthesis/amino acid metabolism (aminoacyl-tRNA biosynthesis; alanine, aspartate and glutamate metabolism; valine, leucine and isoleucine biosynthesis) were observed in males. Similarly, in females many perturbations in amino acid metabolism, nucleotide metabolism, carbohydrate metabolism (pyruvate metabolism; fructose and mannose metabolism), sphingolipid metabolism, bile acid metabolism and microbiome metabolism (propanoate metabolism; butanoate metabolism) were noted. Conclusions: Dietary folate elicits liver metabolome response depending on Aldh1l1 genotype. Funding Sources: NIH, R01